Immune checkpoint inhibitor myocarditis: elucidating the spectrum of disease through endomyocardial biopsy. (25th June 2021) - Palaskas, Nicolas L.; Segura, Ana; Lelenwa, Laura; Siddiqui, Bilal A.; Subudhi, Sumit K.; Lopez‐Mattei, Juan; Durand, Jean B.; Deswal, Anita; Zhao, Bihong; Maximilian Buja, L.; Iliescu, Cezar
Abstract: Aims: Although immune checkpoint inhibitor (ICI) myocarditis carries a high reported mortality, increasing reports of smoldering myocarditis suggest a clinical spectrum of disease. Endomyocardial biopsy (EMB) remains the gold standard for diagnosis of ICI myocarditis, but different pathologic diagnostic criteria exist. The objective of this study was to classify the spectrum of ICI myocarditis and myocardial inflammation by pathology findings on EMB and correlate this with clinical outcomes. Methods and results: All patients who had EMB at MD Anderson Cancer Center between January 2018 and August 2019 for suspected ICI myocarditis were retrospectively reviewed. A grading system (Grades 0–2) based on the degree of inflammatory infiltrate was developed by pathologists. Cardiovascular outcomes and treatment were compared between grades of pathology. We identified 28 patients who had EMB for suspected ICI myocarditis, of which 18 were positive for myocarditis/inflammation. There were four deaths (two in Grade 2 and two in Grade 1), but only one was attributable to myocarditis. Grade 2 patients had no myocarditis‐associated deaths despite having the highest troponin T values (median 2063 pg/mL). Four patients with Grade 1 myocardial inflammation continued ICI without any immunomodulation, and all were alive without adverse cardiovascular events at follow‐up. Conclusion: We defined an EMB grading system for ICI myocarditis encompassing a spectrum of histologic findings of inflammatory infiltrates. A subset of low‐grade myocardial inflammation patients were able to continue ICI without immunosuppressive therapy. Further studies are needed to identify low‐risk patients who can be safely treated with ICI. Abstract : Representative images from each grade of myocarditis/myocardial inflammation. ( A, C, E, G ) Representative haematoxylin & eosin (H&E) images of each grade of myocarditis/myocardial inflammation. ( B, D, F, H ) Representative immunohistochemistry (IHC) images of programmed death ligand 1 (PD‐L1) for each grade of myocarditis. All images taken with magnification 10x (scale bar 100 µm). Cell counts are performed in 20–30 selected high power fields (hpf, 40x lens). Results are expressed as mean per hpf and also converted to mean per 1 mm 2 (1 mm 2  = 4.21 hpf).